Strategi Gerakan Sosial Masyarakat Dalam Konflik Agraria di Kecamatan Membalong Kabupaten Belitung - Purnama Sari, Intan; Ahmad Hariri, Fajar; Deriyanto, Faizal; A Zulkarnain, Ariandi (Journal of Governance Innovation, 2024)
Structural inequality in the agrarian sector is still a problem that continues to be faced by this nation, including in the Bangka Belitung Islands region. The pattern of control, ownership, and use of land that has a new style of colonialism with liberation and capitalism has made agrarian problems not fully improve. Membalong is one area among the agrarian problems in the Bangka Belitung Islands Province due to the chaos of regional planning. The conflict between the community and PT Foresta Lestari Dwikarya is a manifestation of the accumulation of problems at the grassroots which makes this problem increasingly difficult to resolve. Through qualitative research methods with interview, observation, and documentation data collection techniques, this study concludes that community dissatisfaction with land control and the lack of company communication has triggered protests and demands to obtain rights that are considered unilateral claims. The community uses various strategies, such as organizing, lobbying, demonstrations, and reclaiming in demanding justice related to agrarian rights and violence, and involves the parties. Although the government and related institutions have taken steps, the resolution of the conflict which is considered unsatisfactory to all parties has caused tension and the potential for violence that still exists.